Implementasi Pendekatan Integratif dalam Meningkatkan Mahārah Al Istimā' - Nugrahawati, Nurarsyi; Baroroh, R. Umi; Maspeke, Nurul Muthaharaini; Mandaka, Dwi Arian Putra; Wahyuni, Heni (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2025)
The integrative approach in Istimā'  (listening) learning is an approach applied to Istimā' learning by combining the four language skills and other fields of knowledge.  The integrative approach to teaching Istimā' can enhance students' motivation by making learning more relevant and contextual, as well as developing broader skills in various real-life communications. This research discusses Istimā' learning activities with an integrative approach among students in the Arabic Language Education program at the State Islamic University Sunan Kalijaga Yogyakarta. The aim of this research is to explore the integrative approach as an effort to improve the quality of the process and outcomes of Istimā' skill learning for students at the State Islamic University Sunan Kalijaga Yogyakarta. The participants in this study are third-semester students of the 2023 cohort of the Arabic Language Education program at the State Islamic University Sunan Kalijaga Yogyakarta. The research method used is the classroom action research (CAR) method. Data collection techniques include observation and Istimā' learning test results. Data analysis is conducted using qualitative analysis techniques. The research findings indicate that Istimā' learning with an integrative approach can provide meaningful experiences for students, not only enhancing Istimā' skills but also improving speaking, reading, and writing skills. This is evident from the average final grade of students in Istimā' learning, which is 91.63. Through the integrative approach, students are given the opportunity to actively engage in searching for, discovering, and solving problems by involving the four Arabic language skills.